ANALISIS TES KETERAMPILAN BERSASTRA DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYYAH - Noor Zain, Awwaludin Hafizh; Fauzy, Akbar Nur; Hermawan, Acep (STIQ Amuntai, 2024)
The literary proficiency test in learning the Arabic language does not stand alone, but rather has a small part in the test of learning the Arabic language. At the same time, literature tests should be conducted to determine students' in-depth understanding of the Arabic language. With literary activities, students will be trained in Arabic language skills including istima', kalam, kitabah, qira'ah. The purpose of this article is to learn about the basic concepts of literature, learn about literature in learning the Arabic language, and learn about literary proficiency tests in learning the Arabic language. This article specifically discusses literary proficiency tests in assessing Arabic language learning. The article method used is desk research which takes data sources from literary theories. The results of the discussion show that (1) Literature is the expression of human thoughts, ideas, experiences and feelings through written or oral works in an imaginative form that is conveyed by exalting the value of beauty. (2) Literary activities in learning the Arabic language can be classified into four stages, which are information, concept, perspective, and appreciation. (3) The literary proficiency test tool is the same as the verbal and linguistic proficiency test tool, and differs only in content. The answers asked by test questions can consist of choosing answers and compiling your own answers. The contents of this material also make it easier for teachers to prepare and develop literary proficiency tests in learning the Arabic language.